Insulin in Central Nervous System: More than Just a Peripheral Hormone - Ana I. Duarte; Paula I. Moreira; Catarina R. Oliveira (Journal of Aging Research)
Insulin signaling in central nervous system (CNS) has emerged as a novel field of research since decreased brain insulin levels and/or signaling were associated to impaired learning, memory, and age-related neurodegenerative diseases. Thus, besides its well-known role in longevity, insulin may constitute a promising therapy against diabetes- and age-related neurodegenerative disorders. More interestingly, insulin has been also faced as the potential missing link between diabetes and aging in CNS, with Alzheimer's disease (AD) considered as the “brain-type diabetes.” In fact, brain insulin has been shown to regulate both peripheral and central glucose metabolism, neurotransmission, learning, and memory and to be neuroprotective. And a future challenge will be to unravel the complex interactions between aging and diabetes, which, we believe, will allow the development of efficient preventive and therapeutic strategies to overcome age-related diseases and to prolong human “healthy” longevity. Herewith, we aim to integrate the metabolic, neuromodulatory, and neuroprotective roles of insulin in two age-related pathologies: diabetes and AD, both in terms of intracellular signaling and potential therapeutic approach.